Metafora-Metafora Cinta dalam Sakinah Bersamamu Karya Asma Nadia - Ai Kurniati (Balai Bahasa Kalimantan Tengah, 2019)
Asma Nadia is known as a very productive Indonesian woman writer. It is said to be productive because within ten years she produced more than fifty books. The distinctive style of language, especially metaphors of love in the quote of those beautiful wisdom words will be used as data in this paper. This paper aims to describe the metaphors of love in Sakinah Bersamamu by Asma Nadia. The method used is descriptive-qualitative as a problem-solving procedure by describing the language style of metaphors in the quotation of Asma Nadia's wisdom words. Based on the data, there are ten quotes of Asma Nadia's loving wisdom words that utilize the metaphor language style.